Social bioarchaeology - Agarwal, Sabrina C.; Glencross, Bonnie A. (Chichester, West Sussex, [England] Wiley-Blackwell, 2011)
"Social bioarchaeology introduces the exciting and growing biosocial approach in archaeology that challenges the traditional methods of analyzing and interpreting human skeletal remains. Agarwal, Glencross, and the experts assembled in this volume outline the essential components of this research, focusing on the dynamic interactions between humans and their larger social, cultural, and physical environments, and how these analyses increase our understanding of human adaptation. The authors draw upon studies from the Americas, Europe, and the Middle East examining the central themes, theoretical issues, and methodological innovations in the field. Each chapter offers significant new research that integrates elements from biological, behavioural, ecological and social research. This new volume will be a valuable resource for archaeologists, biological anthropologists, paleopathologists, and all researchers with an interest in understanding our social and biological adaptations in a constantly changing global environment"--Provided by publisher.
Building a social bioarchaeology Sabrina C. Agarwal and Bonnie A. Glencross -- The origins of biocultural dimensions in bioarchaeology Molly K. Zuckerman and George J. Armelagos -- Partnerships, pitfalls, and ethical concerns in international bioarchaeology Bethany L. Turner and Valerie A. Andrushko -- The formation of mortuary deposits : implications for understanding mortuary behavior of past populations Estella Weiss-Krejci -- Representativeness and bias in archaeological skeletal samples Mary Jackes -- Sex and gender in bioarchaeological research : theory, method, and interpretation Sandra E. Hollimon -- Population Migration, Variation, and Identity : an Islamic population in Iberia Sonia Zakrzewski -- Life histories of enslaved Africans in colonial New York : a bioarchaeological study of the New York African Burial Ground Autumn R. Barrett and Michael L. Blakey -- The bioarchaeology of leprosy and tuberculosis : a comparative study of perceptions, stigma, diagnosis, and treatment Charlotte Roberts -- Towards a social bioarchaeology of age Joanna Sofaer -- It is not carved in bone : development and plasticity of the aged skeleton Sabrina C. Agarwal and Patrick Beauchesne -- The bioarchaeological investigation of children and childhood / |r Siân E. Halcrow and Nancy Tayles -- Moving from the canary in the coalmine : modeling childhood in Bahrain Judith Littleton -- Skeletal injury across the life course : towards understanding social agency Bonnie A. Glencross -- Diet and dental health through the life course in Roman Italy Tracy L. Prowse.
Includes bibliographical references and index.
Keywords: Human remains (Archaeology).; Social archaeology; Adaptation (Biology) -- History; Human growth -- History; Aging -- History; Life spans (Biology) -- History